2018
DOI: 10.1007/s00231-018-2396-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the dynamics of the flow within freezing water droplets

Abstract: The flow within freezing water droplets is here numerically modelled assuming fixed shape throughout freezing. Three droplets are studied with equal volume but different contact angles and two cases are considered, one including internal natural convection and one where it is excluded, i.e. a case where the effects of density differences is not considered. The shape of the freezing front is similar to experimental observations in the literature and the freezing time is well predicted for colder substrate tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…6 Magnitude of the velocity along four lines at t = 1, 1.5, 2, 2.5, 3 and 4 s (i.e., from 6% up to 25% of the freezing time of the droplet) surface is much larger in comparison with the droplet, the water should have had time to cool off during this time period. Moreover, the flow in this time period show large similarities with the natural convection dominated flow modeled by Karlsson et al (2018), both regarding direction of the vortices and the shape of the freezing front. Two differences between the simulations in Karlsson et al (2018) and the presented experiments, is the direction of the flow in the first seconds of freezing, as well as the fact that the highest magnitude is retrieved in the absolute beginning of freezing, and not a few seconds into the freezing process as observed in the simulations.…”
Section: Internal Flow Patterns In the Freezing Water Dropletmentioning
confidence: 64%
See 3 more Smart Citations
“…6 Magnitude of the velocity along four lines at t = 1, 1.5, 2, 2.5, 3 and 4 s (i.e., from 6% up to 25% of the freezing time of the droplet) surface is much larger in comparison with the droplet, the water should have had time to cool off during this time period. Moreover, the flow in this time period show large similarities with the natural convection dominated flow modeled by Karlsson et al (2018), both regarding direction of the vortices and the shape of the freezing front. Two differences between the simulations in Karlsson et al (2018) and the presented experiments, is the direction of the flow in the first seconds of freezing, as well as the fact that the highest magnitude is retrieved in the absolute beginning of freezing, and not a few seconds into the freezing process as observed in the simulations.…”
Section: Internal Flow Patterns In the Freezing Water Dropletmentioning
confidence: 64%
“…Moreover, the flow in this time period show large similarities with the natural convection dominated flow modeled by Karlsson et al (2018), both regarding direction of the vortices and the shape of the freezing front. Two differences between the simulations in Karlsson et al (2018) and the presented experiments, is the direction of the flow in the first seconds of freezing, as well as the fact that the highest magnitude is retrieved in the absolute beginning of freezing, and not a few seconds into the freezing process as observed in the simulations. This reasoning suggest that natural convection is not the only mechanism inducing internal flow in the freezing droplet.…”
Section: Internal Flow Patterns In the Freezing Water Dropletmentioning
confidence: 64%
See 2 more Smart Citations
“…The phenomenon was first visualized by Kawanami et al [27], who concluded that driving forces that have an influence on the internal flow are temperature gradients, buoyancy forces and surface tension resulting in the Marangoni convection. The internal flow of a water droplet was further numerically studied by Karlsson et al [28,29]. They investigated the buoyancy forces and internal natural convection.…”
Section: Introductionmentioning
confidence: 99%